Molecular and biochemical characterization of carbonic anhydrases of Paracoccidioides - Tomazett,Mariana Vieira (2016)
Abstract Carbonic anhydrases (CA) belong to the family of zinc metalloenzymes that catalyze the reversible hydration of carbon dioxide to bicarbonate. In the present work, we characterized the cDNAs of four Paracoccidioides CAs (CA1, CA2, CA3, and CA4). In the presence of CO2, there was not a significant increase in fungal ca1, ca2 and ca4 gene expression. The ca1 transcript was induced during the mycelium-to-yeast transition, while ca2 and ca4 gene expression was much higher in yeast cells, when compared to mycelium and mycelium-to-yeast transition. The ca1 transcript was induced in yeast cells recovered directly from liver and spleen of infected mice, while transcripts for ca2 and ca4 were down-regulated. Recombinant CA1 (rCA1) and CA4 (rCA4), with 33 kDa and 32 kDa respectively, were obtained from bacteria. The enzymes rCA1 (β-class) and rCA4 (α-class) were characterized regarding pH, temperature, ions and amino acids addition influence. Both enzymes were stable at pHs 7.5-8.5 and temperatures of 30-35 °C. The enzymes were dramatically inhibited by Hg+2 and activated by Zn+2, while only rCA4 was stimulated by Fe2+. Among the amino acids tested (all in L configuration), arginine, lysine, tryptophan and histidine enhanced residual activity of rCA1 and rCA4.